Evolution and optimization method of oriented structure of PAN (Polyacrylonitrile) fiber in thermal stabilization process
By setting specific fiber oxidation heating procedures and using in-situ two-dimensional X-ray diffraction technology, the orientation structure of PAN fibers is optimized, and the importance of fiber orientation evolution and optimization in carbon fiber production is solved, and the development of high-performance carbon fibers is achieved.
Patent Information
- Application Number
- CN202411841458.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-13
AI Technical Summary
During the stabilization and carbonization process of PAN fiber conversion into carbon fiber, the entire process evolution and optimization of fiber orientation have not yet been paid enough attention, resulting in the impact of the mechanical properties of carbon fibers.
By setting a specific warming procedure during fiber oxidation and using in-situ two-dimensional X-ray diffraction technology to reveal the microstructure changes of PAN fibers during drafting and heating, the orientation structure of PAN fibers is optimized. The specific steps include setting the heating program, data analysis, testing the impact of different tensions on fiber shrinkage behavior, using orthogonal experimental design methods to analyze the impact of key parameters on PAN fibers in the stabilization stage, and finally selecting the optimal parameters for optimization.
Real-time monitoring and optimization of the orientation evolution process of PAN fiber, oxidized fiber and carbon fiber is achieved, providing a technical reference for the development of high-performance carbon fibers and improving the mechanical properties of carbon fibers.
Smart Images

Figure CN119785935A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiber thermal stabilization optimization process, and specifically relates to an evolution and optimization method of the orientation structure of PAN fiber in a thermal stabilization process. Background Art
[0002] The process of converting PAN (polyacrylonitrile) fibers into carbon fibers includes two most critical stages: stabilization and carbonization. PAN fibers transform into a trapezoidal structure after the stabilization process and into a turbine-like structure after the carbonization process. The mechanical properties of carbon fibers, such as stiffness or modulus, are highly affected by the orientation of the carbon structure within the fiber. The orientation of the carbon structure refers to the arrangement and alignment of graphite sheets in the fiber microstructure. Carbon fibers are usually composed of graphite nanosheets, and the orientation of these graphite sheets is affected by many factors during the manufacturing process. The orientation of the resulting carbon structure plays a crucial role in determining the modulus of the carbon fiber. In fibers with neatly arranged carbon structures, the modulus along the fiber axis is higher, while the modulus of fibers with randomly or irregularly arranged carbon structures is lower. Therefore, in order to produce high-performance materials with ideal mechanical properties, it is particularly important to control the orientation of the carbon structure in carbon fibers. In the previous experiments, although the orientation of the precursor can be improved by regulating the spinning process, the violent thermal motion of the molecules will produce deorientation during the pre-oxidation process, which will significantly reduce the orientation of the oxidized fiber and is not conducive to the formation of highly oriented carbon fibers, thereby affecting the mechanical properties of the carbon fibers.
[0003] There are many studies on weakening the deorientation effect during the pre-oxidation process. For example, applying moderate stretching during the pre-oxidation process can effectively inhibit the deorientation, thereby improving the overall orientation of the fiber. As early as 1963, Watt et al. found that applying external tension during the thermal stabilization process of fiber transformation can significantly improve the strength and modulus of the fiber. By applying external tension, the fiber shrinkage during the heat treatment process can be significantly inhibited, thereby promoting the orientation of the fiber chain and reducing defects. Chen et al.'s research shows that the mechanical properties of stabilized PAN fibers are closely related to the orientation of PAN chain quasicrystals in the surface area, and further affect the mechanical properties of carbon fibers. Most of the research on improving the stabilization and carbonization process of PAN fibers focuses on optimizing process parameters, such as heating rate, oxidation temperature and ambient atmosphere, to obtain ideal mechanical and structural properties of carbon fibers. For example, Qin et al. pretreated PAN fibers in nitrogen to inhibit the thermal orientation of fibers, thereby significantly improving the tensile strength and Young's modulus of carbon fibers. In addition, researchers have also studied the effects of various additives and surface treatments on the stabilization and carbonization processes, as well as the use of alternative precursors and processing technologies to improve the efficiency and sustainability of carbon fiber production. However, few studies have focused on the overall evolution of fiber orientation during stabilization and carbonization and further optimization of the oriented structure. Summary of the invention
[0004] In response to the current problem of how to optimize the orientation structure during the stabilization and carbonization process of PAN fibers into carbon fibers, the present invention provides the orientation evolution process of PAN fibers, oxidized fibers and carbon fibers, and uses in-situ two-dimensional X-ray diffraction technology to reveal in real time the microstructural changes of PAN fibers during the entire stretching-heating process, providing more experimental evidence and technical references for the development of high-performance carbon fibers.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The evolution and optimization method of the orientation structure of PAN fibers during the thermal stabilization process includes the following steps:
[0007] Step 1, setting of the temperature rise program during fiber oxidation;
[0008] Step 2, data analysis: establish the integral fitting process of the typical XRD two-dimensional diffraction pattern of PAN fiber; calculate the grain size, calculate the interplanar spacing, calculate the crystallinity and calculate the orientation degree;
[0009] Step 3, testing the effect of applying different tensions on the fiber shrinkage behavior;
[0010] Step 4, using the orthogonal experimental design (DOE) method to analyze the key parameters such as temperature, tension / strain and oxidation duration, and systematically study the effects of key parameters on PAN fiber during the stabilization stage;
[0011] Step 5: Select the optimal parameters and complete the optimization.
[0012] Furthermore, the temperature rise program during the fiber oxidation process in step 1 is specifically set as follows:
[0013] The first stage is the rapid heating stage, where the temperature is raised from 25°C to 150°C at a rate of 13.5°C / min;
[0014] The second stage: heating stage, slowly heating to 245℃ at a heating rate of 4.75℃ / min;
[0015] The third stage: stabilization reaction stage, maintaining a constant temperature for 3 hours for oxidation.
[0016] Further, the integral fitting process of establishing a typical XRD two-dimensional diffraction pattern of PAN fiber in step 2 is specifically as follows: the tangent direction of the diffraction arc in the two-dimensional WAXD spectrum is defined as the axis with an azimuth angle of zero. In data analysis, the two-dimensional diffraction pattern is converted into three one-dimensional modes, namely: full-spectrum annular scan, equatorial scan and azimuth scan; wherein the full-spectrum annular scan reflects the crystallinity distribution of the fiber; the equatorial scan provides a peak change orientation along the fiber axis at an angle of 2θ from 10° to 35°, reflecting the crystal size, interplanar spacing and other structural information of the fiber; the azimuth intensity changes with The change in reflects the degree of orientation of the macromolecular chains within the fiber.
[0017] Further, the calculation of the grain size in step 2 is specifically: the grain size Lc of the three-dimensional reflective crystallite is calculated by the Scherer formula, and the calculation formula is as follows:
[0018]
[0019] Where K = 0.9 is a constant factor, λ is the wavelength of the X-ray; FWHM Equ is the half-peak width of the diffraction peak near 2θ≈17°;
[0020] Further, the calculation of the interplanar spacing in step 2 is specifically: the interplanar spacing d value of the quasicrystal is calculated from the 2θ angle obtained from the diffraction spectrum using the Bragg formula, and the calculation formula is as follows:
[0021]
[0022] Where λ is the wavelength of the incident X-ray, θ is half the diffraction angle.
[0023] Further, the calculation of crystallinity in step 2 is specifically: the sample crystallinity is evaluated by the area distribution of the crystal peak and the amorphous region, and the corresponding one-dimensional intensity distribution curve is obtained by performing 2θ scanning integration on the WAXD two-dimensional diffraction pattern. The sum of the peak areas under the crystal diffraction peak represents the crystalline content, and the sum of the peak areas under the amorphous peak represents the amorphous content. The calculation formula is as follows:
[0024]
[0025] Where, f represents the crystallinity of the fiber, f cry and f amor The peak integrated areas represent the crystalline phase and amorphous phase, respectively.
[0026] Further, the orientation degree is calculated in step 2 as follows: the azimuth scanning reflects the orientation degree of the crystals in the sample, the azimuth fitting of the PAN fiber is selected at 17°, and the azimuth fitting of the oxidized and carbon fiber is selected at 25°;
[0027] Therefore, the calculation formula of the orientation coefficient H is as follows:
[0028]
[0029] Among them, FWHM Azi Indicates the maximum half-peak width of the azimuthal scan of the crystal plane.
[0030] Compared with the prior art, the present invention has the following advantages:
[0031] The present invention provides the orientation evolution process of PAN fiber, oxidized fiber and carbon fiber, and uses in-situ two-dimensional X-ray diffraction technology to reveal in real time the microstructural change law of PAN fiber in the entire stretching-heating process, providing a technical reference for the development of high-performance carbon fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 (a) Schematic diagram of the experimental principle; (b) photo of the Linkam stretching hot stage; (c) photo of the in-situ detection two-dimensional WAXD spectrometer.
[0033] Figure 2 It is a schematic diagram of extracting circular scan, equatorial scan and azimuth scan from the WAXD spectrum of PAN fiber.
[0034] Figure 3 These are the peaks and fitting curves in the fiber equatorial direction: (a) PAN fiber; (b) oxidized fiber; (c) carbon fiber.
[0035] Figure 4 These are the WAXD images of PAN fibers at different temperature stages.
[0036] Figure 5 It is the equatorial scan of the fiber; in terms of applied tension, (a), (b,) (c) represent 10MPa, Figures d, e, f represent 20MPa, and Figures g, h, i represent 30MPa; in the stabilization process, a, d, g represent the XRD spectra of the heating stage (Stage I), and b, e, h represent the XRD spectra of the stabilization process at different constant temperature times at 245°C (Stage II); in terms of pre-carbonization and carbonization, c, f, i represent the XRD spectra after carbonization at 500 to 1100°C (Stage III); the oblique dotted line represents the peak movement during the heating process.
[0037] Figure 6Schematic diagram of the shrinkage curve of PAN fiber under three different tensile loads during oxidation.
[0038] Figure 7 are the crystal orientation factors of (a) the 17° peak and (b) the 25° peak during oxidation and carbonization of the fiber under different tensions.
[0039] Figure 8 (a) and (b) are the full factorial design analysis diagrams; (c) and (d) are the orientation degree interaction diagrams; and (d) are the orientation degree main effect diagrams. DETAILED DESCRIPTION
[0040] In order to gain a deeper understanding of the present invention, we will provide a comprehensive and detailed description of the present invention. However, the present invention has multiple implementations and is not limited to the specific examples listed herein. The presentation of these examples is intended to deepen the comprehensive understanding of the disclosure of the present invention.
[0041] Experimental raw materials: dry-jet gel-spun PAN fibers (1k fiber bundles);
[0042] Characterization methods:
[0043] 1. XRD diffraction in-situ characterization: In-situ two-dimensional X-ray measurements were performed on the BRUKER D8 Advance beamline (40KV, 40mA). The two-dimensional surface XRD detector was used to record the diffraction pattern. The distance between the sample and the detector was set to 20 mm, and the wavelength of the incident X-ray was During the WAXD test, the fiber axis is kept in a vertical direction, perpendicular to the incident X-ray beam. The tensile load applied during the oxidation process is controlled by a heatable Linkam tensile fiber accessory. Figure 1 As shown. The original length between the two fixed ends of the Linkam stretching hot stage fiber was 15000 μm, and then the initial length was adjusted to 18000, 16000 and 16000 μm respectively under constant loads initially set at 10, 20 and 30 MPa to ensure the elongation or contraction margin of the fiber. A thin layer of beryllium was placed between the fiber bundle and the heating stage to improve the temperature uniformity so that the fiber was evenly heated and oxidized, and sufficient air was introduced during the oxidation process. The XRD in-situ diffractometer was tested continuously at a time interval of 300 seconds per frame, and the two-dimensional-WAXD spectrum and the curve of the fiber length changing with time were recorded in real time during the entire treatment process. The oxidized fiber was further carbonized in a tubular furnace under a nitrogen atmosphere, and the carbonization temperatures were selected at 500°C, 650°C, 800°C and 1100°C, respectively.
[0044] 2. Mechanical properties test: The tensile properties of the raw fiber and carbon fiber were tested using a tensile tester (XQ-1C), and the linear density of each single fiber was measured using a vibration fineness meter (XD-1, Shanghai New Fiber Instrument Co., Ltd., China). The measured single fiber length was 20 mm, the crosshead speed was 12 mm / min, and 25 groups of samples were tested for each fiber to reduce experimental errors.
[0045] Example 1
[0046] The evolution and optimization method of the orientation structure of PAN fibers during the thermal stabilization process includes the following steps:
[0047] Step 1, setting of the temperature rise program during fiber oxidation;
[0048] The first stage is the rapid heating stage, where the temperature is raised from 25°C to 150°C at a rate of 13.5°C / min;
[0049] The second stage: heating stage, slowly heating to 245℃ at a heating rate of 4.75℃ / min;
[0050] The third stage: stabilization reaction stage, maintaining a constant temperature for 3 hours for oxidation.
[0051] Step 2, data analysis: establish the integral fitting process of the typical XRD two-dimensional diffraction pattern of PAN fiber; calculate the grain size, calculate the interplanar spacing, calculate the crystallinity and calculate the orientation degree;
[0052] Figure 2 The integral fitting process of the typical XRD two-dimensional diffraction pattern of PAN fiber is shown. First, the tangent direction of the diffraction arc in the two-dimensional WAXD spectrum is defined as the axis with an azimuth angle of zero. In data analysis, the two-dimensional diffraction pattern is converted into three one-dimensional modes, namely: full spectrum annular scan, equatorial scan and azimuth scan.
[0053] The full-spectrum annular scan reflects the crystallinity distribution of the fiber; the equatorial scan can provide the peak change orientation of the 2θ angle from 10° to 35° along the fiber axis, reflecting the crystal size, interplanar spacing and other structural information of the fiber; and the change of azimuthal intensity with φ reflects the orientation degree of the macromolecular chains in the fiber. Figure 3 Schematic diagram of 1D WAXD equatorial scans of different fiber stages extracted from the original 2D spectra and peak fitting performed in Jade software is shown.
[0054] The specific calculation of the grain size is: the grain size Lc of the three-dimensional reflection microcrystal is calculated by the Scherer formula, and the calculation formula is as follows:
[0055]
[0056] Where K = 0.9 is a constant factor, λ is the wavelength of the X-ray; FWHM Equ is the half-peak width of the diffraction peak near 2θ≈17°;
[0057] The specific calculation of the interplanar spacing is as follows: the interplanar spacing d of the quasicrystal is calculated from the 2θ angle obtained from the diffraction spectrum using the Bragg formula. The calculation formula is as follows:
[0058]
[0059] Where λ is the wavelength of the incident X-ray, θ is half the diffraction angle.
[0060] The specific calculation of crystallinity is as follows: the sample crystallinity is evaluated by the area distribution of the crystalline peak and the amorphous region. The corresponding one-dimensional intensity distribution curve is obtained by performing 2θ scanning integration on the WAXD two-dimensional diffraction pattern. The sum of the peak areas under the crystal diffraction peak represents the crystalline content, while the sum of the peak areas under the amorphous peak represents the amorphous content. The calculation formula is as follows:
[0061]
[0062] Where, f represents the crystallinity of the fiber, f cry and f amor The peak integrated areas represent the crystalline phase and amorphous phase, respectively.
[0063] The specific calculation of orientation degree is as follows: the azimuth scanning reflects the orientation degree of the crystals in the sample, the azimuth fitting of PAN fiber is selected at 17°, and the azimuth fitting of oxidation and carbon fiber is selected at 25°;
[0064] Therefore, the calculation formula of the orientation coefficient H is as follows:
[0065]
[0066] Among them, FWHM Azi Indicates the maximum half-peak width of the azimuthal scan of the crystal plane.
[0067] Step 3, testing the effect of applying different tensions on the fiber shrinkage behavior;
[0068] Orientation evolution during heat treatment. The orientation of fibers plays a crucial role in determining their tensile properties. During the stabilization and carbonization processes, they undergo a series of complex chemical and physical reactions that affect the orientation of the fiber chains. Figure 4 The two-dimensional WAXD images of PAN fibers before and after heat treatment at different stages are shown. The characteristic diffraction peaks of PAN fibers located near 17 degrees and 29 degrees correspond to the (110) crystal plane and the (020) crystal plane, respectively. Figure 4 The strong scattering observed in the image (around the middle occluder) is due to the generation of nano-scale voids. As the heat treatment proceeds, the 25 degree peak caused by the ladder polymer formed during the stabilization process and the turbulent carbon structure formed after carbonization becomes more and more prominent. The evolution of the XRD spectrum clearly shows the transition from PAN precursor to stabilized and carbon fiber structure. The narrower the azimuthal distribution, the higher its orientation. However, although PAN fibers have excellent chain orientation, the degree of orientation gradually decreases during stabilization and carbonization. Therefore, it is crucial to determine the factors that affect the orientation of the fiber structure and understand the laws of orientation change.
[0069] Figure 5 The equatorial scan fitting diagram of PAN fiber during the heating process and the stable stage is shown. As the temperature increases, the (110) and (020) crystal plane peaks of PAN move to lower diffraction angles, which means that the interplanar spacing d value gradually increases, and at the same time represents the gradual evolution of intramolecular stress. The ratio of the (110) crystal plane to the (020) crystal plane spacing d value is related to the stacking mode of the PAN chain. The ratio of pure polymer PAN precursor fiber is 1.726, indicating that it is cubic stacking; as the temperature rises to 230°C, the ratio increases monotonically to 1.733, which is generally considered to be hexagonal stacking.
[0070] In the rapid heating stage (Stage I), the chemical changes inside the PAN fiber are very weak, and mainly physical changes occur. The initial stage of the pre-oxidation reaction occurs in the disordered amorphous region and gradually transforms to the ordered region. When the temperature exceeds 230°C, the ordered region begins to react and exhibits violent characteristics, and complex chemical changes occur in the air environment, including cyclization, oxidation and dehydration reactions. The reason why the reaction is initiated in the amorphous region is that the comonomers are mainly concentrated in the amorphous region, which provides sufficient reactants for the reaction; secondly, the molecular chains in the amorphous region are disordered, and the electrostatic coupling force between the cyano groups and other intermolecular forces are relatively weak, which makes it easier for the molecular chains to adjust their conception to undergo reactions such as cyclization, and oxygen can also easily diffuse into the amorphous region; thirdly, compared with the amorphous region, the molecular chains in the crystalline region are neatly arranged and the intermolecular forces are stronger, so the difficulty of adjusting the molecular chain conception and oxygen diffusion in the crystalline region is significantly increased.
[0071] exist Figure 5In the XRD curves shown in (b)(e)(h), the intensity of the characteristic peaks of PAN (2θ~17° and 29°) is significantly weakened and eventually disappears, while the aromatic structure at 2θ~25° is significantly enhanced. This indicates that in the heating stage (Stage II), the fiber structure has undergone major changes due to chemical reactions, and the -C≡N group of the PAN molecular chain has transformed into a -C=N group, resulting in the transformation of the one-dimensional linear molecular chain into a more stable two-dimensional trapezoidal structure, and the (100) face crystal structure has been destroyed. In the heating stage, with the increase of tension stretching, the cyclization reaction rate is accelerated accordingly. As the pre-oxidation temperature continues to rise, the trapezoidal crystals increase, the crystal form gradually improves, and the disappearance of the old structure and the establishment of the new structure are proceeding simultaneously. The stabilized fiber is further carbonized in a nitrogen atmosphere at a temperature above 400°C.
[0072] In the stabilization reaction stage (Stage III), non-carbon elements such as nitrogen, oxygen and hydrogen in the fiber gradually disappear, and the carbon content increases to more than 90wt%. It can also be seen from the X-ray diffraction curve that at this time, only a single peak of aromatic and turbulent carbon structures at 2θ~25° is included.
[0073] The corresponding length changes of the fibers oxidized by heating in the first and second stages after being subjected to different drawing tensions are shown in Figure 2. Figure 6 As shown. The change in fiber length is divided into entropy shrinkage and reaction shrinkage. During the entropy shrinkage process, PAN fibers will undergo several thermal transitions, including β and α transitions. The β transition (usually 80-100 ° C) is related to the molecular motion sequence in the para-crystalline phase, while the α transition (usually 130-150 ° C) is attributed to the glass transition and crystal / crystal transition of the amorphous region, such as the transition from cubic stacking to hexagonal stacking structure. The main chemical reaction shrinkage behavior occurs during the stabilization reaction above 230 ° C. At this stage, the applied tension has a great influence on the shrinkage behavior of the fiber. Under different tensions of 10, 20 and 30 MPa, the reaction shrinkage rates are 10.3%, 2.4% and -10.2% (negative values indicate stretching), respectively. If the tension applied in the physical shrinkage stage is too small and the relaxation is excessive, the orientation degree of the fiber is low and high-strength fibers cannot be obtained; but if the applied tension is too large, it will induce higher internal tension, resulting in the generation of internal tensile defects, which will remain in the final carbon fiber product, and high-strength carbon fiber preparation cannot be achieved.
[0074] Table 1 summarizes the crystal size and crystallinity of PAN fibers at different heat treatment stages calculated from the WAXD fitting spectra. The crystal size of PAN precursor fibers is about 7 nm and the crystallinity is about 56%.
[0075] At temperatures below 130 °C, no obvious structural changes were observed. However, as the treatment temperature increased from 130 °C to 190 °C, the crystal size increased from Increase to This is equivalent to an increase of 10-20%. In addition, the crystallinity also increased from 56% to 60-63%, an increase of 8-14%. The results show that when the α transition temperature is exceeded, the amorphous PAN chain will recrystallize. As can be seen from Table 1, both the grain size and crystallinity reach their highest at 190°C, and then begin to decline with the increase of the pre-oxidation temperature. This change pattern is closely related to the cohesive state between molecules. When the PAN molecular chain undergoes the initial pre-oxidation process, a large number of nitrile group dipole reactions increase, which may lead to the growth, accumulation and reorganization of small grains, thereby causing a simultaneous increase in grain size and crystallinity. At a temperature of around 210°C, the PAN crystal parameters maintained a short plateau period; however, when the temperature exceeded 230°C, the pre-oxidation reaction entered the later stage, the PAN crystals rapidly amorphized, the crystals melted, and the crystallinity and crystal size decreased sharply. During the stabilization process, the characteristic diffraction peak of PAN is significantly weakened, the molecular chain of AN structure is rapidly transformed into a ladder polymer structure, and the calculation of crystal size is also transferred from the (110) crystal plane of PAN to the (002) crystal plane of the formed aromatic polymer or turbulent carbon structure. After the carbonized PAN fiber is treated in the temperature range of 500 to 1100 ° C, the crystal size is stable at There is not much difference in the fiber crystal size and crystallinity under different tension drawing, and they basically maintain the same evolution trend.
[0076] Table 1 Crystal size and crystallinity of PAN fibers at different heat treatment stages
[0077]
[0078] The orientation of the fiber is a key factor in determining its tensile properties, especially for the modulus. This is because the polymer chains of the fiber are arranged in parallel along the orientation direction. When the axial fracture occurs, the proportion of the main valence bonds of the highly oriented fiber that are broken increases significantly. Since the strength of the main valence bond is about 50 times that of the van der Waals force, the tensile strength and modulus of the precursor will increase with the increase of its orientation. In the process of structural transformation from precursor to carbon fiber, due to the complex chemical and physical changes that occur, it becomes very important to understand the relationship between fiber orientation, processing parameters, and the final stabilization and carbonization of the fiber. The orientation of PAN crystals is based on the maximum half-peak width (FWHM) scanned by the (110, 2θ~17°) crystal plane azimuth angle. Azi Similarly, the orientation of aromatic polymers and turbocarbon structures was evaluated based on the FWHM of the azimuthal scan of the (002, 2θ~25°) crystal plane. Azi ) is obtained. FWHM AziThe smaller the value, the better the orientation of the fiber. Table 2 lists the half-peak width of the orientation of PAN fibers at different processing stages under different applied tensions such as 10MPa, 20MPa and 30MPa. The half-peak width represents the orientation degree, that is, the maximum half-peak width FWHM of the azimuth scanning. Azi In addition, in the comparison of three different tensions, a set of comparative experiments was added, that is, 30MPa tension was applied to PAN fiber at the initial stage of oxidation process until the temperature rose to 245℃ for 15 minutes, and then the tension was quickly reduced to 10MPa. The other conditions were the same as the formal experiment. The corresponding test data are also listed in Table 2. According to the fiber orientation data in Table 2, the corresponding Herman orientation factor was calculated and plotted as Figure 7 .
[0079] When the temperature is lower than 230°C (stage I), physical changes mainly occur, and the overall orientation degree of PAN fibers is relatively high. This is because the tension stretching in this stage effectively suppresses the influence of physical shrinkage and alleviates the molecular chain deorientation behavior. At the same time, the orientation of PAN fibers shows a significant dependence on the applied stretching force. Under a tension of 30MPa, the orientation of the fiber can be well maintained, and the orientation coefficient is higher than 0.95. When the applied tension is reduced to 20MPa, the final orientation coefficient is about 0.94. When the tension is further reduced to 10MPa, a significant decrease in the orientation coefficient can be observed. At 210°C, under constant tensions of 10MPa, 20MPa and 30MPa, the FWHM of PAN fibers Azi (17°) are 14.83°, 10.62° and 9.32° respectively.
[0080] Table 4-2 Crystal orientation degree (FWHM) of PAN fiber 17 degree peak and 25 degree peak during oxidation and carbonization Azi )
[0081]
[0082] When the temperature exceeds 230°C (stage II), the cyclization reaction is more intense, and the oxidation reaction and cyclization reaction release heat together, resulting in the breakage of the PAN macromolecular chain and the formation of numerous structural defects. The stabilization reaction will cause a significant decrease in the orientation of the PAN crystals. Assuming a comparable degree of stabilization at the same processing stage, applying greater tension to the PAN fiber helps maintain a better orientation. The orientation decay observed during the stabilization of PAN fibers can be attributed to various factors, including physical and chemical changes. The transition from PAN to aromatic polymers results in fundamental structural changes, and the applied tension is key to maintaining or causing good orientation of the aromatic ring structure. In the case of aromatic polymers ( Figure 7b), its orientation is highly dependent on the applied tension, but remains almost unchanged during the entire stabilization process. The greater the applied tension, the better the orientation of the aromatic polymer. However, the applied drawing force must be within a suitable range that does not damage the crystal structure of the original fiber, otherwise the gel network skeleton formed during the gel spinning process will be stretched due to excessive tension, affecting the crystallinity and other structures of the original fiber. After stabilization at 245°C for 3 hours, the FWHM of the stabilized PAN fiber under constant tensions of 10MPa, 20MPa and 30MPa Azi (25°) are 38.92°, 35.87° and 33.83° respectively. For PAN fibers stabilized at 30MPa tension and then reduced to 10MPa, their orientation is only lower than that of fibers stabilized at 30MPa. In summary, the study found that higher oxidative stretching force can effectively promote the stretching and orientation rearrangement of polymer chains, and is one of the most important processing factors for achieving good fiber orientation.
[0083] The oxidized PAN fibers continued to be carbonized. In the third stage, the fibers were carbonized in a tubular furnace under a nitrogen atmosphere at temperatures of 650°C, 800°C and 1100°C. The resulting carbon fibers were then analyzed by WAXD to determine the orientation of the turbine carbon structure. Before the final carbonization, the fibers were pre-carbonized at 500°C to eliminate the main non-carbon elements such as nitrogen and oxygen, which would be converted into by-products such as tar gas. Therefore, the orientation change of the pre-carbonized structure was not obvious enough, but higher applied tensions could still produce better orientation. After further carbonization at 650°C and higher temperatures, the orientation differences became increasingly obvious. After carbonization at 1100°C, the final FWHM of the carbon fibers with constant tensions of 10MPa, 20MPa and 30MPa during the oxidation process were Azi (25°) are 41.64°, 36.36° and 35.29° respectively. It can be seen that the pre-oxidation process can keep the fiber in a good orientation during the subsequent high-temperature carbonization process. Therefore, the regulation of orientation in the high-temperature stage of the late pre-oxidation is the key factor in obtaining high-performance carbon fibers.
[0084] According to the above analysis, the loss of the main orientation of PAN crystals and the formation of neatly arranged aromatic polymers occur simultaneously during the oxidation stabilization process. Azi (25°) and FWHM of oxidized fibers Azi (25°) shows the same trend, indicating that the orientation of the carbon structure is inherited from the formation of aromatic polymers. In order to obtain high modulus carbon fibers, the orientation of the turbine carbon structure must be improved, which depends on the orientation of the aromatic polymers formed during the stabilization process.
[0085] Step 4, using the orthogonal experimental design (DOE) method to analyze the key parameters such as temperature, tension / strain and oxidation duration, and systematically study the effects of key parameters on PAN fiber during the stabilization stage;
[0086] Temperature, tension / strain and oxidation duration are key parameters in the stabilization phase of PAN fibers. . By varying and optimizing these parameters, the carbon fiber product can be endowed with the desired ideal mechanical properties. In order to systematically study the effects of these parameters, this section uses the orthogonal experimental design (DOE) method for analysis. In this method, different levels of each parameter are selected and systematically varied, and the resulting data are analyzed using statistical methods. By conducting an orthogonal experimental analysis, the effects of each parameter and the interactions between them can be determined. This allows the stabilization process to be optimized, thereby improving the mechanical properties of the final carbon fiber product.
[0087] The DOE test was conducted in two stages. The first step was to select two experimental variables, temperature and tension, based on the previously known experimental influencing factors, and consider two different levels of each variable. A full factorial design (n k The experimental factors (k) and their respective levels (n) are studied in this paper. Table 1 shows the number of experiments designed with two factors, two levels and two center points and the experimental results (2 2 +2=6), and then the main effects and the interactive effects of influencing factors were determined based on the six experimental results with different condition combinations.
[0088] Table 3 Full factorial design (experimental conditions and results)
[0089]
[0090]
[0091] Here, the aromatization index (AI) indicates the degree of conversion of the PAN linear molecular chain to the ladder polymer structure during the stabilization process. The calculation of the aromatization index depends on the characterization method. For WAXD spectra, the AI index is calculated, where I 17 and I 25 They are the peak intensities at 2θ=17° and 25°, respectively. Here, the AI value can also be calculated using the fitted peak area of the XRD spectrum after the fiber is completely oxidized, and then fibers with the same degree of oxidation under different conditions are selected for orientation comparison, and a full factorial design analysis is performed. In order to achieve the same degree of stabilization, when the temperature changes from 220°C, 240°C to 260°C, the oxidation constant temperature time is shortened from 5 hours to 2 hours and 1 hour, respectively. The last column in the table lists the results of each experiment. The FWHM of (002, 2θ~25°) is selected here. Azi The values are used to compare the orientation degree of stabilized fibers.
[0092]
[0093] The main effects plots and factor interaction plots associated with the factor design process are shown below. Figure 8 . The two factors of temperature and tension were analyzed, and their respective effects on the orientation degree of oxidized fibers were studied. The interaction between the two factors was not statistically significant (P value ≥ 0.05), indicating that their combined effect on the orientation results was negligible; the main effect plot of the two factors showed that the effect of tension on the orientation degree was significantly stronger, while the effect of temperature was much weaker. Based on these results, a response surface model was established, and its coefficient of determination (R 2 ) is 98.35%, which indicates a high accuracy in predicting the orientation degree of oxidized fibers based on the temperature and tension settings.
[0094] The experimental results show that the intrinsic orientation structure of the oxidized fibers is directly related to the stretching tension applied during the oxidation process. Specifically, compared with fibers oxidized under a tension of 10 MPa, the orientation structure of fibers oxidized under a higher tension of 30 MPa is significantly improved. The higher the temperature of the pre-oxidation reaction process, the faster the reaction rate and the shorter the time to reach the final optimal orientation degree can be seen from the AI fitting data, but too high a temperature will affect the dynamic balance of crystal melting and cyclization reactions during the oxidation reaction. Therefore, regulating key factors such as oxidation temperature, residence time and tension drawing can provide reliable experimental data for optimizing fiber oxidation process parameters.
[0095] Step 5: Select the optimal parameters and complete the optimization.
[0096] Optimization of oxidation process conditions. In the continuous production process of fibers, several continuous heating zones are usually set up, the purpose of which is to gradually increase the tension when the fibers pass through higher temperatures, thereby maintaining the orientation of the fibers. This is very important for the final properties of carbon fibers, because the higher the degree of orientation, the higher the fiber strength and stiffness. However, the precursor cannot be directly subjected to high tension. First, it may break directly because a certain stable structure has not been formed in the oxidation reaction stage; second, it is easy to produce internal tensile defects. Combined with the experimental contents of the previous two parts, in order to determine the optimal drawing tension and other parameter conditions during the fiber oxidation process, this section conducts experiments by designing a temperature gradient. Here, two temperature zones from 220℃ to 260℃ and three temperature zones from 220℃, 240℃ to 260℃ are selected for testing. The fibers are oxidized at corresponding tension levels at different temperatures. The tension level applied in the first stable stage may not be the final value set, but can be gradually increased to the set value in the subsequent temperature zones. This approach is also to avoid the fiber from being unable to withstand the tension in the initial stage and breaking directly. Table 4 summarizes the detailed experimental conditions and lists the final orientation half-peak width of the stable fiber.
[0097] Table 4 Orientation half-peak width of oxidized PAN fibers under different temperature gradient conditions
[0098]
[0099]
[0100] During the stabilization process, the choice of oxidation time and drawing tension is very important to achieve a high degree of orientation of PAN fibers. According to the results of previous orthogonal experiments, the oxidation time of each temperature zone was set to 40 minutes during the two-temperature zone stabilization process. In the initial low-temperature oxidation stage of the fiber, a tension of 30MPa was used, which was the highest tension applicable to this stage determined based on previous experiments. These specific parameters were selected to ensure that the fiber was adequately stabilized to maintain its orientation while avoiding damage to the fiber due to excessive oxidation or excessive stretching. To determine the optimal tension in the high-temperature stage, continuous tensions of 45, 50, 55, 60 and 65MPa were selected for testing. The results show that with the increase of tension, the orientation of the fiber gradually increases. However, it was observed that when the tension exceeded 55MPa, the fiber became very unstable and easily broke. Therefore, the optimal tension in the high-temperature stage was determined to be 55MPa. Under this condition, FWHM Azi (25°) is 31.99°, which is significantly lower than the 33.83° of single temperature zone stabilization in Table 2. In the three-temperature zone stabilization process, the duration of each temperature zone is 40 minutes. Compared with the two-temperature zone stabilization process, the fiber is not easy to break when subjected to the same tension and can maintain good orientation. Under the temperature gradient of 220-240-260℃ and the tension gradient of 30-55-65MPa, the preferred orientation degree of the oxidized fiber is the best.
[0101] In summary, the present invention reveals the orientation evolution process from PAN precursor fiber to stabilized fiber and then to carbonized fiber, and also establishes an efficient and time-saving method for optimizing stabilization conditions. These results provide valuable insights into the role of drawing tension and oxidation temperature on the orientation and crystal structure of PAN fibers during oxidation, and show that controlling tension during oxidation is extremely important for determining the intrinsic orientation structure of fibers, which directly affects the final structure of carbon fibers. During the thermal stabilization of PAN fibers, the fiber orientation increases with increasing tension, and the final orientation coefficient of oxidized fibers can be as high as 0.81 under a tension of 30MPa. After the carbonization temperature exceeds 500℃, the orientation degree of the obtained carbon fiber is consistent with that of the stabilized fiber, indicating that the orientation of the carbon structure is inherited from the orientation of the aromatic polymer. The higher the orientation degree of the fiber structure, the greater the tensile modulus of the carbon fiber. Orthogonal experimental analysis shows that there is a significant positive correlation between drawing tension and orientation coefficient. Therefore, a three-temperature zone continuous oxidation process was simulated to increase tension, and it was found that the oxidized fiber can stably withstand a tension of 65MPa and obtain an optimal orientation factor of 0.83. These results indicate that during the pre-oxidation process of PAN fibers, the occurrence of cyclization, oxidation, and dehydrogenation reactions are significantly affected by oxidation temperature, oxidation time, and oxidation stretching. Selecting appropriate fiber stretching tension in the corresponding temperature range is beneficial to improving the ultimate strength of carbon fibers.
[0102] These findings of the present invention are of great significance for optimizing processing conditions to produce high-performance carbon fibers with ideal orientation and crystal structure. The use of in-situ two-dimensional XRD diffraction provides a powerful tool for characterizing the structural changes of fibers during oxidation and can be used to guide the optimization of processing parameters.
[0103] The contents not described in detail in the specification of the present invention belong to the prior art known to the professional and technical personnel in the field. Although the illustrative specific embodiments of the present invention are described above to facilitate the understanding of the present invention by the technical personnel in the field, it should be clear that the present invention is not limited to the scope of the specific embodiments. For the ordinary technical personnel in the field, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.
Claims
1. Evolution and optimization method of oriented structure of PAN fiber in thermal stabilization process, characterized in that: The following steps are involved: Step 1, setting of the temperature rise program during fiber oxidation; Step 2, data analysis: establishing the integral fitting process of the typical XRD two-dimensional diffraction pattern of PAN fiber; Calculate grain size, calculate interplanar spacing, calculate crystallinity and calculate orientation; Step 3, testing the effect of applying different tensions on the fiber shrinkage behavior; Step 4, using orthogonal experimental design method to analyze the key parameters such as temperature, tension / strain and oxidation duration, and systematically study the influence of key parameters on PAN fiber during the stabilization stage; Step 5: Select the optimal parameters and complete the optimization.
2. The method for evolving and optimizing the orientation structure of PAN fibers during a thermal stabilization process according to claim 1, characterized in that: The specific setting of the temperature increase program during the fiber oxidation process in step 1 is: The first stage is the rapid heating stage, where the temperature is raised from 25°C to 150°C at a rate of 13.5°C / min; The second stage: heating stage, slowly heating to 245℃ at a heating rate of 4.75℃ / min; The third stage: stabilization reaction stage, maintaining a constant temperature for 3 hours for oxidation.
3. The method for evolving and optimizing the orientation structure of PAN fibers during a thermal stabilization process according to claim 1, characterized in that: The integral fitting process of establishing the typical XRD two-dimensional diffraction pattern of PAN fiber in step 2 is specifically as follows: the tangent direction of the diffraction arc in the two-dimensional WAXD spectrum is defined as the axis with an azimuth angle of zero. In data analysis, the two-dimensional diffraction pattern is converted into three one-dimensional modes, namely: full-spectrum annular scan, equatorial scan and azimuth scan; wherein the full-spectrum annular scan reflects the crystallinity distribution of the fiber; the equatorial scan provides a peak change orientation along the fiber axis at an angle of 2θ from 10° to 35°, reflecting the crystal size and interplanar spacing information of the fiber; the azimuth intensity changes with The change in reflects the degree of orientation of the macromolecular chains within the fiber.
4. The method for evolving and optimizing the orientation structure of PAN fibers during a thermal stabilization process according to claim 1, characterized in that: The specific calculation of the grain size in step 2 is: the grain size Lc of the three-dimensional reflective microcrystal is calculated by the Scherer formula, and the calculation formula is as follows: Where K = 0.9 is a constant factor, λ is the wavelength of the X-ray; FWHM Equ It is the half-width of the diffraction peak near 2θ≈17°.
5. The method for evolving and optimizing the orientation structure of PAN fibers during a thermal stabilization process according to claim 1, characterized in that: The calculation of the interplanar spacing in step 2 is specifically: the interplanar spacing d value of the quasicrystal is calculated from the 2θ angle obtained from the diffraction spectrum using the Bragg formula, and the calculation formula is as follows: Where λ is the wavelength of the incident X-ray, θ is half the diffraction angle.
6. The method for evolving and optimizing the orientation structure of PAN fibers during a thermal stabilization process according to claim 1, characterized in that: The crystallinity calculation in step 2 is specifically as follows: the sample crystallinity is evaluated by the area distribution of the crystal peak and the amorphous region, and the corresponding one-dimensional intensity distribution curve is obtained by performing 2θ scanning integration on the WAXD two-dimensional diffraction pattern. The sum of the peak areas under the crystal diffraction peak represents the crystalline content, and the sum of the peak areas under the amorphous peak represents the amorphous content. The calculation formula is as follows: Where, f represents the crystallinity of the fiber, f cry and f amor The peak integrated areas represent the crystalline phase and amorphous phase, respectively.
7. The method for evolving and optimizing the orientation structure of PAN fibers during a thermal stabilization process according to claim 1, characterized in that: The specific calculation of the orientation degree in step 2 is as follows: the azimuth scanning reflects the orientation degree of the crystals in the sample, the azimuth fitting of the PAN fiber is selected at 17°, and the azimuth fitting of the oxidation and carbon fiber is selected at 25°; Therefore, the calculation formula of the orientation coefficient H is as follows: Among them, FWHM Azi Indicates the maximum half-peak width of the azimuthal scan of the crystal plane.
8. The method for evolving and optimizing the orientation structure of PAN fibers during a thermal stabilization process according to claim 1, characterized in that: Under a tension of 30 MPa, the final orientation coefficient of the oxidized fibers was 0.
81.
9. The method for evolving and optimizing the orientation structure of PAN fibers during a thermal stabilization process according to claim 1, characterized in that: The stable tension that the oxidized fiber can withstand is 65MPa, and the optimal orientation factor is 0.
83.
10. The method for evolving and optimizing the orientation structure of PAN fibers during a thermal stabilization process according to claim 1, characterized in that: The optimum tension is 55MPa.
Citation Information
Patent Citations
Preparation method of polyacrylonitrile-based carbon fiber and prepared polyacrylonitrile-based carbon fiber
CN115707806A
Polyacrylonitrile initial-stage thermal-oxidative stabilization fiber as well as preparation method and application of polyacrylonitrile initial-stage thermal-oxidative stabilization fiber
CN115928268A
Carbon fiber and method for producing the same
JP2013249570A
Carbon fiber bundle and its manufacturing method
JP5907321B1
A process for producing polymer fiber and polymer fiber made therefrom
US20240117529A1
Cited By
In-situ characterization method and system of carbon fiber spinning process
CN121558616A
An in-situ characterization method and system for carbon fiber spinning process
CN121558616B